Growth of late preterm infants fed nutrient-enriched formula to 120 days corrected age—A randomized controlled trial - Best, Karen P.; Yelland, Lisa N.; Collins, Carmel T.; McPhee, Andrew J.; Rogers, Geraint B.; Choo, Jocelyn; Gibson, Robert A.; Murguia-Peniche, Teresa; Varghese, Jojy; Cooper, Timothy R.; Makrides, Maria (Frontiers in Pediatrics, 2023)
Objectives: We aimed to compare the effects of nutrient-enriched formula with standard term formula on rate of body weight gain of late preterm infants appropriately grown for gestational age. Study Design: A multi-center, randomized, controlled trial. Late preterm infants (34-37weeks’ gestation), with weight appropriate for gestational age (AGA), were randomized to nutrient enriched formula (NEF) with increased calories (22 kcal/30mL) from protein, added bovine milk fat globule membrane, vitamin D and butyrate or standard term formula 20kcal/30ml (STF). Breastfed term infants were enrolled as an observational reference group (BFR). Primary outcome was rate of body weight gain from enrollment to 120 days corrected age (d/CA). Planned sample size was 100 infants per group. Secondary outcomes included body composition, weight, head circumference and length gain, and medically confirmed adverse events to 365 d/CA. Results: The trial was terminated early due to recruitment challenges and sample size was substantially reduced. 40 infants were randomized to NEF (n=22) and STF (n=18). 39 infants were enrolled in the BFR group. At 120 d/CA there was no evidence of a difference in weight gain between randomized groups (mean difference 1.77g/day, 95% CI −1.63 to 5.18, P=0.31). Secondary outcomes showed a significant reduction in risk of infectious illness in the NEF group at 120 d/CA (relative risk 0.37 [95% CI 0.16 to 0.85], P=0.02). Conclusion: We saw no difference in rate of body weight gain between AGA late preterm infants fed NEF compared to STF. Results should be interpreted with caution due to small sample size